STRATEGI ORANG TUA DALAM MENGATUR SCREEN TIME ANAK USIA 5-6 TAHUN - Lailatul Umania; Isti Rusdiyani; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine parents' strategies in managing screen time for children aged 5-6 years in Kampung Sambilawang, Margasari Village, Pulo Ampel District, Serang Regency, as well as its impact on children's development. The study employed a qualitative approach with a descriptive method. The research subjects were parents of children aged 5-6 years. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model. The results indicate that parents' strategies in managing screen time include limiting the duration of use, selecting and monitoring content, accompanying children during screen time, and redirecting children to non-digital activities. Screen time has positive impacts, including increased knowledge and cognitive abilities, but also leads to negative effects such as gadget dependency, reduced social interaction, decreased physical activity, and tantrum behavior. Supporting factors include the existence of gadget usage rules and family support, while inhibiting factors include parents' limited time and children's dependency on gadgets.